The Influence of 'Product-and-Non-Product Dimension' and Country of Origin Dimension on Brand Image - Sirnamora, Bilson; Sari, Hasrini; Heryanto, Jony (SBM ITB, 2008)
There is no doubt the contribution of country-of-origin (COO) dimension for product value or brand value and to influence consumer behavior. However, if we confronted with the question about which is the most powerful one among brand and COO, we still have no answer until now. There are also differences among researchers about the linkage of individual brand and COO. Some experts put COO as a dimenstion of brand equity. Other experts put COO into super position or ‘halo effect’ that influences all of the brand attributes that shape brand image. In this article, the authors develop conceptual framework to find the relative influence of COO and ‘product-and-non-product’ dimension on brand image. We generate eleven hypotheses and propose new construct called ‘nation disconfirmation’. Together with conclusion, we propose the managerial and academic implications of our conceptual framework. Keywords: brand image, brand equity